Nonsteroidal anti-inflammatory drugs in chronic pain : implications of new data for clinical practice - Ho, Kok Yuen (2019)
COX2-selective and nonselective (ns) nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used for chronic pain management. There are marked differences in the risk of adverse gastrointestinal (GI) and cardiovascular (CV) events among different NSAIDs. In 2017, publication of two randomized controlled trials and an individual patient-data meta-analysis provided robust data on the relative GI and CV tolerability profiles of currently available NSAIDs. The PRECISION study showed similar CV-event rates with celecoxib vs naproxen and ibuprofen, but GI tolerability was better for celecoxib. In the CONCERN study of high-GI-risk patients, celecoxib was associated with fewer adverse GI-tract events than naproxen. The meta-analysis showed no significant difference between celecoxib and ns-NSAIDs in the rate of acute myocardial infarction, and celecoxib was the only COX2-selective NSAID with a lower risk of adverse CV and GI events vs ns-NSAIDs. These data add to the body of knowledge about the relative tolerability of different NSAIDs and were used to propose an updated treatment algorithm. The decision about whether to use an NSAID and which one should be based on a patient’s risk of developing adverse GI and CV events. Lower- and upper-GI-tract events need to be considered. Celecoxib has a better lower-GI-tract tolerability profile than ns-NSAIDs plus a proton-pump inhibitor. In addition, the latest data suggest that long-term use of celecoxib 200 mg/day may be appropriate for patients at increased CV risk.